Jump to content

Recommended Posts

Posted
If 1 = 2, then

 

X = Y

 

X - Y = 0

 

2(X - Y) = 0

 

X - Y = 2(X - Y)

 

(X - Y) / (X - Y) = (2(X-Y)) / (X - Y)

 

1 = 2

 

I can shorten all that for you.

 

If 1=2

Then 1=2

 

You really don't need all that fiddly stuff in the middle when you started with that IF statement.

Create an account or sign in to comment

You need to be a member in order to leave a comment

Create an account

Sign up for a new account in our community. It's easy!

Register a new account

Sign in

Already have an account? Sign in here.

Sign In Now
×
×
  • Create New...